2015
DOI: 10.1111/jeb.12787
|View full text |Cite
|
Sign up to set email alerts
|

Severe outbreeding and inbreeding depression maintain mating system differentiation inEpipactis(Orchidaceae)

Abstract: In hermaphroditic plants, theory for mating system evolution predicts that populations will evolve to either complete autonomous selfing (AS) or complete outcrossing, depending on the balance between automatic selection favouring self-fertilization and costs resulting from inbreeding depression (ID). Theory also predicts that selection for selfing can occur rapidly and is driven by purging of genetic load and the loss of ID. Therefore, selfing species are predicted to have low levels of ID or even to suffer fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 67 publications
(102 reference statements)
0
9
0
Order By: Relevance
“…Because several studies have shown that Epipactis species can rapidly evolve towards selfing (Pedersen and Ehlers , Squirrell et al , Brys and Jacquemyn ) and because selfing itself can act as a reproductive barrier preventing interspecific mating (Brys et al ), we investigated whether the capacity to self autonomously differed between the two ecotypes. Two months before flowering, ten individuals were selected in one forest and one dune population and transferred to a pollinator‐free greenhouse.…”
Section: Methodsmentioning
confidence: 99%
“…Because several studies have shown that Epipactis species can rapidly evolve towards selfing (Pedersen and Ehlers , Squirrell et al , Brys and Jacquemyn ) and because selfing itself can act as a reproductive barrier preventing interspecific mating (Brys et al ), we investigated whether the capacity to self autonomously differed between the two ecotypes. Two months before flowering, ten individuals were selected in one forest and one dune population and transferred to a pollinator‐free greenhouse.…”
Section: Methodsmentioning
confidence: 99%
“…This expression, proposed by Sletvold et al (2012) or Delmas et al (2014), derives and is equivalent to that from Ågren and Schemske (1993). The inbreeding depression coefficient ranges between 1 and −1; if W o > W s , δ values are positive and inbreeding depression exists, while in W i > W o , δ values are negative and outbreeding depression occurs (Brys and Jacquemyn, 2016). Inbreeding depression coefficients for each color morph and site were calculated separately at different life stages (partial inbreeding depression coefficients) and then, cumulative inbreeding depression coefficients were also calculated.…”
Section: Inbreeding Depression Throughout Life Cyclementioning
confidence: 99%
“…Negative fitness responses resulting from mating between individuals from highly divergent populations of copepods were noted by Hwang et al (). Other examples of outbreeding depression in varied species of plants are provided by Fenster and Gallaway (), Waser et al (), Goto et al (), and Brys and Jacquemyn (). In general, however, outbreeding depression is thought to be less of a concern when implementing conservation measures such as genetic introgression (Miller et al , Whiteley et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Hedrick et al () provided evidence for the declining effect of genetic introgression on the Isle Royale population of wolves after only 2 or 3 generations. Whereas heterosis is expected to increase individual fitness, it can also result in outbreeding depression (Fenster and Gallaway , Waser et al , Goto et al , Waller , Brys and Jacquemyn ). Depending on the mechanisms, outbreeding depression may not become evident until generations subsequent to the first filial (F1) generation (Pickup et al , Waller ).…”
Section: Introductionmentioning
confidence: 99%